Lead and Cadmium Ions Mitigation in Soil using Calcium Carbide Waste-Carbonised Lophira Alata Sawdust Composite (CCW-CLAS) as Immobilizing Agent - Moses*, Okponmwense; Asekhame, Queen Omone (Aceh International Journal of Science and Technology, 2022)
Soil contamination with heavy metals is a global environmental matter of interest due to its thinkable dangers to humans, environmental health, and the ecosystem preceding shortfalls in agricultural produce and dangerous health outcomes as they penetrate the food chain. This study aimed to mitigate lead and cadmium ions contaminant in soil using calcium carbide waste-carbonized lophira alata sawdust composite (CCW-CLAS). Contaminated soil samples were collected from Evbareke spare parts market, Benin City, Edo state Nigeria, using a grid sampling method at a depth of 0-20cm with a soil auger. 50% W/W of the powdered calcium carbide waste and lophira alata sawdust was placed in a ceramic crucible, put into a muffle furnace, and heated at 350oC for 3 hours. The X-ray diffraction analysis for the calcium carbide wastecarbonized lophira alata sawdust composite (CCW-CLAS) revealed that it was made up of predominantly calcite fraction (55.0%), portlandite (25.0%), coesite (7.3%), muscovite (6.7%), dolomite (4.0%) and lime (2.1%) this was supported by FTIR analysis. SEM analysis revealed that calcium carbide waste-carbonized lophira alata sawdust composite (CCW-CLAS) possesses a rough surface with a pore of varied size and irregular shape. The contaminated soil from the Evbareke spare parts market was heavily polluted with petroleum hydrocarbons, and the soil was highly saline with low C.E.C. The soil texture was loamy sand; as the amount of CCW-CLAS increased in the soil, the amount of cadmium and lead ions that was releasable in the soil reduced, indicating that CCW-CLAS was effective in immobilizing cadmium and lead ions. The optimum amount of the amender in the contaminated soil to immobilize lead ion was 4% w/w, and cadmium ion was 2%.